The Male Gaze in Internet Advertising: Content Analysis of Axe Indonesia's Collaboration with Enzy Storia on Instagram - Prasiani Purnama Sari (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Instagram serves as a unique platform for businesses to engage consumers, market products, and convert visitors into buyers. While brands typically tailor their visual presentation to align with the brand persona and the sex/gender of their target audience, Axe Indonesia, in contrast, collaborated with Enzy Storia as an influencer on social media and even at off-network events, thereby indicating the presence of the male gaze in this collaboration. This qualitative study, employing a content analysis approach, aims to understand how the male gaze is reflected in Axe Indonesia's advertising content involving Enzy Storia on Instagram to generate engagement. The findings reveal the existence of visual representation, gender construction, and Enzy Storia's contribution in this collaboration. The male gaze in the visuals is further supported by audio elements, captions, and copy that objectify women